What is this asking I have no idea
The correct answer is C: 1/(x + 4)(x - 5)
Why? Well, let's first simplify x^2 - 3x - 10 and x^2 + x - 12; the two denominators. Each of these should become an (x +/- number), and to figure out the number, as well as whether it is positive or negative, we can do a simple trick
Look at the factors of the right number (In this case, -10 and -12)
-10 -12
1 * -10 1 * -12
-1 * 10 -1 * 12
-2 * 5 -2 * 6
2 * -5 2 * -6
-3 * 4
4 * -3
Now for part 2
Which of these pairs add up to the middle number? One of the pairs of -10 should make -3, and likewise, one of the pairs of -12 should make 1 (when x has no number in front of it you may safely assume it is 1).
2 - 5 = -3 and 4 - 3 = 1, so we now know that the 2 fraction equations simplified is
x + 2 / (x + 2)(x - 5) * x - 3/(x -3)(x + 4)
Notice anything repeating? As long as they are apart of the same fraction, we can cross out anything that has the same x - number. Crossing out both x + 2 and x - 3, we now simply have x - 5 * x + 4. Because we crossed out both numerators, the top numbers both become 1, thus giving our answer, C.
Answer:
0.083 repeating
Step-by-step explanation:
The chance of getting 3 on the first spin is 1/6 because there are 6 possible outcomes and 1/2 on the second spin because 1,3,5 are all odds and 2,4,6 are even and when you multiple them together you get 0.083 repeating.
The answer for the given equation is x = 3.5.
<u>Step-by-step explanation</u>:
Given, 2 / 3 (3x + 6) = 4x + 3
Step 1:
Rearranging the given equation by subtracting the right side of the equation to the left side.
2 / 3 (3x + 6) - 4x + 3 = 0
Step 2:
Taking out the like terms, the equation becomes
(2 / 3)
3 (x + 2) - (4x - 3) = 0
⇒ 2 (x + 2) - (4x - 3) = 0
Step 3:
Solving the equation for the value of x,
⇒ 2x + 4 - 4x + 3 = 0
⇒ -2x + 7 = 0
⇒ -2x = -7
⇒ x = 7 / 2 = 3.5.
Hence the value of x = 3.5.
MLN is an isosceles triangle
ML = MN
3x = x + 8
Subtract x from both sides
2x = 8
Divide both sides by 2
x = 4
MN = 4 + 8 = 12
Answer
A. 12